Assessment of underground water quality: A case study of Jhansi city, Uttar Pardesh, India - and Anshu Dhaka3, *Sandeep Arya1, Vinit Kumar1, Minakshi2 (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Seasonal variation on physicochemical parameters of groundwater in Jhansi city of Bundelkhand region, Uttar Pradesh was determined. Groundwater samples were taken from ten locations of city. The quality analysis has been made through the temperature (12°C-32°C), pH (6.5-8.4), EC (0.2-0.6 mmhos), TDS (110-280 mg/l), DO(4.3-6.9 mg/l), total alkalinity (118-230 mg/l), total hardness (230-610 mg/l), carbonate (85-165 mg/l), bicarbonate (116-210 mg/l) and chloride (23-85 mg/l). Parameters alkalinity, pH, DO, bicarbonate were found to be negatively correlated and EC, TDS, total hardness, carbonate, chloride were show a positive correlation with temperature.